THE DEVELOPMENT GARMENT PATTERN FOR THE ELDERLY - Soodsung, Irada; Ratnidhikunanoon, Saowanee; Ariyakuare, Kittisak; Yadee, Sudakan; Wanphet, Thitaporn (Journal of Social Science and Cultural, 2024)
This research is a mixed methods research quantitative and qualitative to design and develop apparel patterns for the elderly and to study consumer satisfaction towards apparel patterns for the elderly. The sample group used in the study was a 5- product design expert together with a group of elderly people aged from 60 to 80 years old residing in Dusit District, Bangkok. Numder 100 people. The tool used to collect data is a satisfaction questionnaire and 6 types of apparel prototypes for the elderly. Percentage statistics, the arithmetic mean and standard deviation were used for data analysis. The results of the study found that Six styles of clothing for the elderly include: 1) Short-sleeved shirt style, open back, front slit, Hawaiian collar, has 2 front pockets. 2) Three-quarter sleeve shirt style, loose, front slit, 4 buttons, shirt collar, has a pocket on the left front. 3) Long sleeve shirt style, loose, front slit, shirt collar, slit on the cuff, and has a pocket on the left front. 4) Shorts style, flared legs, side pockets, back scales, side elastic waist, front zipper. 5) Three-quarters pants style, straight leg ends, straight fit, side pockets, 2 front pleats, back scales, side elastic waist, front zipper and 6) Long pants style: straight leg ends, straight fit, side pockets, 1 front pleat, back scale, elasticated waistband on the side, front zipper. Satisfaction with clothing style For the elderly, it was found that respondents were most satisfied with the three-quarter-length pants style, followed by the three-quarter sleeve shirt style. trousers pattern long sleeve shirt pattern shorts pattern and short sleeve shirt styles with average values of 4.47, 4.46, 4.30, 4.25, 4.00 and 3.99, respectively.